(3GdMOGFb GdhQOjI aj efGbH GdCFeI GdRjOjIs - (3MejO Hf CMeO GdnenMpqdj GdgeOGfqj, CHh YHO Gddg MSGe GdOjf, GdeYQha HGdbGVj GdTgjO,J (B652 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV YdfjG CfhGQ GdgOGjI , hRMRMfG HdWag Yf eOGQL GdZhGjI HJCjjOg Yf GdEfNOGY HJehjgGJ CQHGH GdVdGdI s
(3BNQgG (B:s
(3bhdg (B: (3fSCd Gddg SHMGfg JhajbkG hfMeOg Ydi LRjd GdfhGd , hfSCdg GdUdGI Ydi eMeO hBdg NjQ Bd Je GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJs
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs